The importance of wastewater treatment in shipbuilding industry - Akanlar, F. Tolga; Celebi, U. Bugra; Vardar, Nurten (INDERSCIENCE ENTERPRISES LTD, 2011)
There is a huge amount of wastewater outcome during the ship production and repair processes in shipyards. Especially production processes (blasting, welding, painting, machining and metalworking), repair processes (hull washing) and painting processes (paint removal) create a huge amount of wastewater. In addition to these, open area processes of ship repair and maintenance cause stormwater runoff resulting in an increase in wastewater. The flow prevention of these wastewaters to sea or water sources is extremely important. Hazardous waste containing wastewaters should be separated according to waste management principles and discharged accordingly. In this study, the possible wastewater outcome from shipyard production processes is investigated and necessary methods for the wastewater treatment are discussed.
Keywords: shipyard waste; shipyard process; wastewater; wastewater treatment; waste minimisation; SHIPYARD; Environmental Sciences & Ecology